Bioaccumulation of pharmaceuticals and personal care products in the unionid mussel Lasmigona costata in a river receiving wastewater effluent. (March 2016) - de Solla, S.R.; Gilroy, È.A.M.; Klinck, J.S.; King, L.E.; McInnis, R.; Struger, J.; Backus, S.M.; Gillis, P.L.
Abstract: Freshwater mussels are frequently found in rivers receiving effluent from wastewater treatment plants (WWTP), and there is strong evidence that poor water quality is deleterious to freshwater mussel populations. WWTPs are among the main sources of pharmaceuticals and personal care products (PPCPs) in surface waters. We monitored 145 PPCPs in wild and caged mussels both upstream and downstream of the Kitchener WWTP in the Grand River, Ontario, as well as 118 PPCPs in water samples. Our objectives were to characterize the seasonal changes in PPCP concentrations in water, to calculate bioaccumulation factors (BAFs) of PPCPs in mussels, and to determine the chemical and physical properties of PPCPs driving the bioaccumulation. Seventy PPCPs were detected in water, and concentrations were highest in the summer or early fall, which corresponded to low river flow. Forty-three PPCPs from many pharmaceutical classes were detected in mussel tissues, including stimulants, a contrasting agent, anti-inflammatory drugs, anti-bacterial agents, antibiotics, antidepressants, antihistamines, progestins, and illicit drugs such as cocaine and amphetamines. The BAFs ranged from 0.66 for metformin to 32 022 for sertraline. Using partial least squares to predict BAFs based upon chemical properties, log KOC, Log KOW, and fugacity ratio (sediment) all had similar and positive loadings with BAFs (R 2 X = 0.70; caged mussels). BAFs of PPCPs in mussels were predictable from fugacity models that estimate bioconcentration factors using log KOW . Our study demonstrated that mussels readily bioaccumulate PPCPs, in a manner consistent with expectations based upon BCF models and the chemical characteristics of each compound. Highlights: Bioaccumulation of 145 PPCPs were measured in mussels upstream and downstream of WWTPs. 43 PPCPs from many classes were detected in mussel tissue. Seasonality in PPCP in water meant exposures were highest in late summer during low river flow. The BAFs ranged from 0.66 for metformin to 32 022 for sertraline. BAFs were predictable from log KOC, Log KOW, and fugacity ratio (R 2 X = 0.70).